Тенденції розвитку українського книговидання та контенту в цифрову епоху - Мина, Жанна; Лильо, Марта (Видавництво Львівської політехніки, 2025)
The abstracts examines the digital transformation of Ukrainian book publishing аmid technological change. It highlights the rise of e-books and audiobooks, the use of social media for promotion, and modern copywriting strategies like personalization, SEO, and voice search adaptation. The study also examines multichannel marketing—video, podcasts, and blogs—to engage new audiences. Emphasis is placed on digital tools' role in promoting Ukrainian literature, enhancing accessibility, and expanding its global presence, supporting cultural growth.
Keywords: книговидання; цифрова трансформація; копірайтинг; соціальні мережі; контент